2014
DOI: 10.1021/jf501464g
|View full text |Cite
|
Sign up to set email alerts
|

Development of Stable Isotope Dilution Assays for the Quantitation of Amadori Compounds in Foods

Abstract: During thermal processing of foods, reducing carbohydrates and amino acids may form 1-amino-1-desoxyketoses named Amadori rearrangement products after the Italian chemist Mario Amadori. Although these compounds are transient intermediates of the Maillard reaction, they are often used as suitable markers to measure the extent of a thermal food processing, such as for spray-dried milk or dried fruits. Several methods are already available in the literature for their quantitation, but measurements are often done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…For example, in 2014, Meitinger et al. quantified seven Amadori compounds in cocoa beans including Fru‐Leu and Fru‐Lle, but the two isomers coeluted in a single peak . In 2014, Wanhong Zhou et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in 2014, Meitinger et al. quantified seven Amadori compounds in cocoa beans including Fru‐Leu and Fru‐Lle, but the two isomers coeluted in a single peak . In 2014, Wanhong Zhou et al.…”
Section: Introductionmentioning
confidence: 99%
“…Until 2 years ago, Amadori compounds in complex matrices such as foods and tobacco were quantified using HPLC-MS/MS. For example, in 2014, Meitinger et al quantified seven Amadori compounds in cocoa beans including Fru-Leu and Fru-Lle, but the two isomers coeluted in a single peak [14]. In 2014, Wanhong Zhou et al quantified two important Amadori compounds in cigarettes [15].…”
Section: Introductionmentioning
confidence: 99%
“…This reaction can be easily taken place not only in the body but also in foods (Meitinger et al, 2014). Amadori products generated from glucose and amino acids might contribute to animal's health because it has been reported that this compounds have several biological effects such as antioxidant (Ide et al, 1999), antihyperglycemia (Ha et al, 2011), and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the formation of lysine-based, peptide-bound Heyns compounds has been clarified (Rene, Kathein, Evelyn, & Thomas, 2008). Recently, Troise et al (2015) analyzed Fru-Ala and Fru-Leu Heyns compounds via HPLC, and Meitinger et al carried out the investigation of Fru-Leu Heyns compounds in foods (Meitinger, Hartmann, & Schieberle, 2014;Troise, Fiore, Roviello, Monti, & Fogliano, 2015). This work is important in the characterization of fructose-based Heyns products of Maillard reactions and is helpful for the analysis of Amadori products of peptide-specific Maillard reactions.…”
Section: Introductionmentioning
confidence: 99%